ANALISIS FAKTOR PERILAKU DAN PENGALAMAN DIGITAL TERHADAP MINAT PENGGUNAAN LAYANAN BI–FAST DI KOTA DENPASAR - komang kiska jendra; Gusi Putu Lestara Permana (Universitas Prof.Hazairin,SH Bengkulu, 2026)
This study aims to analyze behavioral factors and digital experiences that influence the intention to use BI–FAST services in Denpasar City. The research focuses on the influence of Perceived Usefulness, Subjective Norms, and Self-Efficacy on Cashless Payment Usage. A quantitative approach with a survey method was employed, and primary data were collected through a Google Form questionnaire distributed to BI–FAST users in Denpasar City using purposive sampling with a minimum of 125 respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to examine the relationships among latent variables. The results show that Perceived Usefulness and Subjective Norms have a significant positive effect on Self-Efficacy. Furthermore, Perceived Usefulness, Subjective Norms, and Self-Efficacy are proven to have a positive influence on Cashless Payment Usage. These findings confirm that perceived benefits, social influence, and users’ self-confidence play an important role in increasing BI–FAST adoption. Based on the analysis, it can be concluded that improving perceived usefulness, social support, and user self-efficacy can enhance the intensity of BI–FAST usage in Denpasar City. This research is expected to provide practical contributions for financial institutions in designing strategies to expand the adoption of digital payment systems, while also enriching the literature on user behavior in the context of modern payment services in Indonesia.